2017
DOI: 10.1002/jemt.22925
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the cellular makeup and progenitor potential of palatal connective tissues

Abstract: The present study investigated the regenerative potential of connective tissues harvested from two palatal areas widely used as donor sites for muco-gingival surgical approaches. Connective tissue grafts (CTGs) were obtained by de-epithelialisation of a free gingival graft (deCTG) and by a split flap approach from a previous donor site (reCTG). Two types of mesenchymal stem cell (MSCs) were isolated and were named de-epithelialised MSCs (deMSCs) and re-entry MSCs (reMSCs). The cells were characterised and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The present study also demonstrated that after the de‐epithelialization procedures, epithelial remnants were partly observed in superficial portions of DGG as stated in the previous studies (Pall et al., 2017; Romano et al., 2017; Azar, Rojas, Mandalunis, et al, 2019). The effect of epithelial remnants on long‐term RC outcomes of DGG procedures remains unknown (Romano et al., 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study also demonstrated that after the de‐epithelialization procedures, epithelial remnants were partly observed in superficial portions of DGG as stated in the previous studies (Pall et al., 2017; Romano et al., 2017; Azar, Rojas, Mandalunis, et al, 2019). The effect of epithelial remnants on long‐term RC outcomes of DGG procedures remains unknown (Romano et al., 2017).…”
Section: Discussionsupporting
confidence: 91%
“…DGG approaches obtained with both extra‐oral (Harris, 2003; McLeod et al., 2009; Zucchelli et al., 2010; de Sanctis et al, 2011; Vieira et al., 2017) and intra‐oral (Ozcelik et al., 2016) de‐epithelialization of the FGGs‐ in combination with CAF or TUN procedures have been shown promising results in periodontal plastic surgeries (McLeod et al., 2009; Zucchelli et al., 2010, 2014; Ozcelik et al., 2016). Because of the fact that DGG has been demonstrated to have higher amount of fibrous connective tissue and less amount of fatty and glandular tissue compared to conventional SCTG substitutes (Bertl et al., 2015; Pall et al., 2017), DGG has been found to associate with decreased shrinkage of the grafts and increased GT (Zuhr et al., 2014). Tavelli et al.…”
Section: Discussionmentioning
confidence: 99%
“…Colonies with more than 50 cells were counted. CFU‐F efficiency was estimated based on formula: CFU‐F efficiency = (counted CFU‐F/cells originally seeded) × 100 (Castro‐Malaspina et al, ; Pall et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Following culture for 48‐hr, the spheroid aggregates were harvested and transferred to 6‐well plates (CytoOne, Cell Culture, Mineapolis) coated with 0.1% gelatin (Sigma‐Aldrich, St. Louis) in PBS (Sigma‐Aldrich, St. Louis) to facilitate attachment of the aggregates and promote MSC migration. Following culture for 7 days, the area of migration was calculated following measurement (NIS‐Elements D3.0 Laboratory Imaging software) of aggregate size and the MSC coverage area, using this formula: migration area = MSC migration area—aggregate size (Pall et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In the oral cavity, human MSCs have been isolated and characterized from odontogenic and non-odontogenic origins, permitting the harvesting of healthy tissues during dental surgical procedures. Thus, a subset of cells displaying MSC properties and osteogenic properties have been described from gingival connective tissue [gingival mesenchymal stem/progenitor cells (GMSCs)] (Yang et al, 2013), oral periosteum of the palate (Caballero et al, 2010;Ceccarelli et al, 2016), the lower and upper vestibule (Ceccarelli et al, 2016), palatal connective tissue (Roman et al, 2013;Páll et al, 2015, Pall et al, 2017, and adipose stem cells from buccal fat pad (Farré-Guasch et al, 2010). Recently, palatal periosteum-derived MSCs cells, cultivated under serum-and xeno-free conditions, and cells were able to retain stem cell properties (Naung et al, 2019).…”
Section: Third Generation Of Palatal Reconstruction: Bone Bioengineeringmentioning
confidence: 99%